2019
DOI: 10.1002/clc.23266
|View full text |Cite
|
Sign up to set email alerts
|

The association between hyperuricemia and coronary artery calcification development: A systematic review and meta‐analysis

Abstract: Hyperuricemia coincides with coronary artery calcification (CAC) development, but the role of serum uric acid (SUA) as a risk factor for CAC remains unclear. The objective of this study was to gain an insight into the association between SUA and CAC in adults by performing a meta‐analysis. MEDLINE, EMBASE, the Cochrane Library, and EBSCO (CINAHL) were searched for relevant observational studies published until 2 June 2019. Studies were included only if they reported data on CAC presence (Agatston score > 0) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…This systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [ 19 ]. A protocol was not registered, since it is not mandatory, as per several recommendations [ 20 , 21 ]. On 26 July 2022, PubMed, Scopus, Web of Science, and Google Scholar were searched for articles that report the presentation of EES in the pediatric population (children and young adolescents <21 years of age).…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [ 19 ]. A protocol was not registered, since it is not mandatory, as per several recommendations [ 20 , 21 ]. On 26 July 2022, PubMed, Scopus, Web of Science, and Google Scholar were searched for articles that report the presentation of EES in the pediatric population (children and young adolescents <21 years of age).…”
Section: Methodsmentioning
confidence: 99%
“…Previous meta-analyses have identified a correlation between uric acid levels and a variety of CHD outcomes. Previous research by 5 revealed a correlation between uric acid levels and the risk of poor clinical outcomes in the form of coronary artery calcification in the CHD patient population; with every 1 mg/dl uric acid increase, the risk of CAC increased by 31%. Furthermore, the study by 12 found a correlation between uric acid levels and the prognosis of CHD mortality; with every 1 mg/dl uric acid increase, mortality increased by 9%, but the missing adjustment needed for diuretic use and renal functioning was identified as a shortcoming in their meta-analysis.…”
Section: Discussionmentioning
confidence: 96%
“…It is not clear how uric acid is correlated with CHD, but several studies suggest that elevated uric acid, also known as hyperuricemia, increases CHD risk by inducing endothelial dysfunction, oxidative stress, and interconnected inflammatory mechanisms. 5 , 6 The clinical manifestations of CHD contribute to increased circulating uric acid levels in the arterial tissue, including coronary arteries. 7 Impaired tissue reperfusion due to CHD activates circulating xanthine oxidase enzymes in the endothelium, leading to an increase in uric acid levels and, as a result, endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Another study was found a positive relationship between serum UA and CAC in 663 asymptomatic middle-aged patients 12 . A recent systematic review and meta-analysis reported that serum UA is associated with increased risk of CAC development and progression in asymptomatic subjects [1,28] and is an independent predictor for the development of moderate CAC in subjects with no or minimal CAC [29]. Although the molecular mechanism is not fully understood, it is suggested that UA as pro-oxidant may stimulate VSMC production of superoxide radical by COX-2 and thus contribute to atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%